Docência na educação infantil: normativas para a constituição do trabalho das auxiliares de creche - Almeida, Gleiciele Magela de (2023)
The focus of this research is the teaching work of nursery assistants who work together with teachers at Children’s Education public institutions. Along with the movement of Children’s Education expansion, it characterizes the configuration of this playing filed and gathers two categories of teachers — nursery assistant and teacher — regarding the work shared with little kids. In this context, it problematizes the provisions municipal policies of nursery assistants to work in this stage. Therefore, the study aims at understanding the constitution of the assistants’ teaching work based on Espírito Santo (ES) municipal public policies. Underpinned in a bakhtinian theoretical-methodological perspective, a qualitative exploratory approach research is developed, with procedures of normative document analysis that guide the nursery assistants work and semi-structured interviews with the managers in charge of Children’s Education and with trade unions representing this category. In accordance with the research data, the districts face some challenges in order to guarantee better working conditions for the Children Education teachers. This finding is linked to the creation of a significant amount of laws and notices that, mostly, institute poor working conditions for the nursery assistants. By these means, it is observed that this category’s historical journey in the field of Children’s Education is initiated from a diversity of conceptions, justifications and motivations, which highlight the care strategies related to little kids. This demonstrates that, even with all the changes made in the last decades, this position is still in a formulation process in the state of Espírito Santo, at times, disregarding the progress achieved in the field of Children’s Education. Consequently, the study acknowledges the complexity regarding circumscribing the teaching work of those nursery assistants, bearing in mind the particularities and diversity of elements that compose its configuration. As such, it is noticed that the challenge to assess the functional compositions aiming at potentiating Children’s Education as a field that takes into consideration the children’s specificities and that assures the value of the teachers’ work, remains in the horizon of public policies.